2013
DOI: 10.1038/npp.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Single Administration of Intranasal Oxytocin on the Recognition of Basic Emotions in Humans: A Meta-Analysis

Abstract: Many studies have highlighted the potential of oxytocin (OT) to enhance facial affect recognition in healthy humans. However, inconsistencies have emerged with regard to the influence of OT on the recognition of specific emotional expressions (happy, angry, fear, surprise, disgust, and sadness). In this study, we conducted a meta-analysis of seven studies comprising 381 research participants (71 females) examining responses to the basic emotion types to assess whether OT enhances the recognition of emotion fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
196
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(219 citation statements)
references
References 46 publications
16
196
6
1
Order By: Relevance
“…Moreover, oxytocin decreased trusting expectations for participants with anxious attachment but had no effect in less anxiously attached participants (Bartz et al, 2011b). Consistent with our findings in the context of social cooperation, a recent meta-analysis of facial recognition (Shahrestani et al, 2013) revealed distinct oxytocin effects in implicit (o300 ms, fast, automatic processing) and explicit (4300 ms, slow, deliberated, controlled processing) contexts. Oxytocin enhances recognition of happy and angry expressions under implicit recognition (intuitive system) but facilitates recognition of fear expressions with longer durations of exposure (reflective system).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, oxytocin decreased trusting expectations for participants with anxious attachment but had no effect in less anxiously attached participants (Bartz et al, 2011b). Consistent with our findings in the context of social cooperation, a recent meta-analysis of facial recognition (Shahrestani et al, 2013) revealed distinct oxytocin effects in implicit (o300 ms, fast, automatic processing) and explicit (4300 ms, slow, deliberated, controlled processing) contexts. Oxytocin enhances recognition of happy and angry expressions under implicit recognition (intuitive system) but facilitates recognition of fear expressions with longer durations of exposure (reflective system).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, behavioral studies have shown evidence for distinct oxytocin effects on fast and slow emotion recognition. Oxytocin facilitated recognition of happy expression during fast exposure but enhanced recognition of fearful expression during slow recognition (Shahrestani et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, we found that oxytocin (40 IU) improved emotion recognition only in women. A previous study reported that oxytocin improves recognition of a range of emotions (Shahrestani et al, 2013) and another study found that the effects of oxytocin on emotional stimuli may differ in women and men (Domes et al, 2010). The full profile of subjective and behavioral effects of oxytocin remains to be determined.…”
Section: Discussionmentioning
confidence: 95%
“…Single doses of intranasal oxytocin can also produce prosocial, anxiolytic, and affiliative effects in healthy adults (Bos et al, 2011;Lim and Young, 2006). For example, oxytocin has been shown to increase trust and generosity (Kosfeld et al, 2005;Zak et al, 2007), reduce responses to social stressors (Heinrichs et al, 2003), increase positive communication (Ditzen et al, 2009), and, like MDMA, enhance recognition of positive emotional states and dampen responses to negative emotions in others (Di Simplicio et al, 2009;Domes et al, 2007a,b;Marsh et al, 2010;Shahrestani et al, 2013). On the other hand, other studies have failed to detect prosocial effects of oxytocin, and indeed, found that it can produce antisocial effects such as feelings of envy and mistrust (Bartz et al, 2011a;Declerck et al, 2010;Shamay-Tsoory et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed an increase in pMCC activity only under OXT and only in social stimulus-paired trials. OXT has been shown to increase social cognition in the face of both positive and negative stimuli (Shahrestani et al, 2013). It follows that OXT could generally increase the perception of social-related stimuli during fear conditioning.…”
Section: Discussionmentioning
confidence: 99%